Konsep Dasar Konseling Kelompok - Siti Wahyuni (IAIN Padangsidimpuan, 2018)
Group counseling is a counseling process undertaken by a counselor with several dynamic counselors to facilitate counselee development and / or assist counselees in overcoming problems they face together. While the purpose of group counseling for a counselee can develop a variety of skills that in essence increase confidence (self confidence) and trust in others. Group counseling has two functions, namely the curative service function; namely services directed to overcome the problems experienced by individuals, as well as the function of preventive services; namely counseling services directed to prevent the occurrence of problems in the individual self.Keywords: Group counseling, curative and preventive.